Tracking of the origin and history of fluids in the Hellisheiði and Nesjavellir geothermal fields, Iceland - Biying Chen; Finlay M. Stuart; Chris M. Holdsworth; Stuart M.V. Gilfillan (Chemical Geology, 2026)

Helium diffusion and (U-Th)/He thermochronology of pyromorphite - Yan Ma; Finlay M. Stuart; Ying Wang; Jianzhang Pang; Lei Liu; Liene Spruzeniece (Chemical Geology, 2026)

The geochemical and isotopic composition of the Miocene Vestfirðir basalts, Northwest Iceland: Tracking the evolution of the Iceland mantle plume - Ugur Balci; Emma Martin-Roberts; Björn Hardarson; J. Godfrey Fitton; Valerie Olive; Ryan Ickert; Darren F. Mark; Finlay M. Stuart (Chemical Geology, 2026)

Polymetallic nodules offshore NE Greenland: links to Fram Strait opening and local hydrothermal activity - Dmitrii Zastrozhnov; John M. Millett; Sverre Planke; Stéphane Polteau; Adriano Mazzini; Derek Fabel; Finlay Stuart; Ana Carracedo; Luigia Di Nicola; Valerie Olive; Nina Lebedeva-Ivanova; Iakov Gogin; et al. (Sedimentary Geology, 2026)

Surface uplift of the Eastern Alps. Was it much faster than we thought? - Kurt Stüwe; Jörg Robl; Gerit Gradwohl; Derek Fabel; Finlay M. Stuart; Lukas Plan; Zsófia Ruszkiczay-Rüdiger (Earth-Science Reviews, 2026)

Changing volatile emissions and sources along the Ethiopian Rift - Abate A. Melaku; Gemechu B. Teferi; Takele Mihretie; Snorri Gudbrandsson; Yared Sinetebeb; Peter H. Barry; Tobias P. Fischer; Finlay M. Stuart; Ugur Balci; Sæmundur A. Halldórsson; Chris J. Ballentine; Darren J. Hillegonds; et al. (Earth and Planetary Science Letters, 2026)

Chemistry and He isotope systematics of olivine as tracers of source in mantle xenoliths from Harrat Hutaymah and Harrat Kishb Cenozoic lava fields, Western Saudi Arabia - Ahmed Hasan Ahmed; Abdel-Kader M. Moghazi; Finlay M. Stuart; Shehta Abdallah; Moustafa Hashad; Kamal A. Ali (Geochemistry, 2025)

He, Ne, and Ar isotope systematics in Chang’e-5 plagioclase reveal diffusive loss and reirradiation processes - Xuhang Zhang; Fei Su; Guillaume Avice; David V. Bekaert; Tomoya Obase; Yuta Otsuki; Finlay M. Stuart; Yingnan Zhang; Jiayan Nie; Xiaoguang Li; Runqing Zhou; Ziheng Liu; et al. (Earth and Planetary Science Letters, 2025)

Reconstructing coalbed methane accumulation history in the Qinshui Basin using noble gas isotopes - Zhelin Zhang; Biying Chen; Yi Liu; Zhanjie Xu; Finlay M. Stuart; Sheng Xu (Applied Geochemistry, 2025)

New He-O-Sr-Nd isotopes and chronology of Quaternary lavas from the Kula volcanic field (western Türkiye): Implications for temporal changes in the magma source - Duru Cesur; Halim Mutlu; Ercan Aldanmaz; Finlay M. Stuart; Ana Carracedo; Robert M. Ellam; Nilgün Güleç (Chemical Geology, 2025)

Ice-burial history and early Holocene thinning of the Scandinavian Ice Sheet at Gaustatoppen, southern Norway - Jane Lund Andersen; Nathaniel A. Lifton; Henriette Linge; Finlay Stuart; Jesper Olsen; Vivi K. Pedersen (Quaternary Science Reviews, 2025)

Presence of non-solar derived krypton and xenon unveiled by Chang'e-5 lunar soils - Xuhang Zhang; Fei Su; Guillaume Avice; Finlay M. Stuart; Yuanyuan Zheng; Ziheng Liu; Wei Guo; Thomas Smith; Runchuan Liu; Chao Lu; Ye He; Jiannan Li; et al. (Earth and Planetary Science Letters, 2024)

Late Cretaceous-Eocene exhumation of the northern Lhasa terrane and topographic implications for the Central Tibet - Gaoyuan Sun; Hugh D. Sinclair; Cristina Persano; Finlay M. Stuart; Xiumian Hu (Lithos, 2024)

Assessing the potential for CO2 storage in shallow coal seams using gas geochemistry: A case study from Qinshui Basin, North China - Biying Chen; Lujia Fang; Zhanjie Xu; Finlay M. Stuart; Guofu Li; Sheng Xu (International Journal of Greenhouse Gas Control, 2024)

Inter-laboratory re-determination of the atmospheric 22Ne/20Ne - Domokos Györe; Hirochika Sumino; Inseok Yang; László Palcsu; Elemér László; M. Cole Bishop; Sujoy Mukhopadhyay; Finlay M. Stuart (Chemical Geology, 2024)

Intensive chemical weathering in the Arctic during the Miocene Climatic Optimum - Adrian M. Hall; Dan N. Barfod; H. Albert Gilg; Finlay M. Stuart; Pertti Sarala; Thair Al-Ani (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The role of mantle melting in granite-associated hydrothermal systems: He–Ar isotopes in fluids responsible for Sn–Ag–Pb–Zn mineralization in northeast China - Zhenhua Zhou; Jingwen Mao; Finlay M. Stuart; Xinkai Chen; Simon A. Wilde; Hegen Ouyang; Xu Gao; Jiaqi Zhao (Mineralium Deposita, 2023)

The exhumation history of the middle Hsuehshan Range, Taiwan, as revealed by zircon thermochronological modeling - Chase J. Shyu; Eh Tan; Linda A. Kirstein; Finlay M. Stuart; Yue-Gau Chen (Tectonophysics, 2023)

A review of noble gas geochemistry in natural gas from sedimentary basins in China - Biying Chen; Yi Liu; Lujia Fang; Sheng Xu; Finlay M. Stuart; Congqiang Liu (Journal of Asian Earth Sciences, 2023)

A two phase escarpment evolution of the Red Sea margin of southwestern Saudi Arabia. Insights from low-temperature apatite thermochronology - Syed Ali Turab; Kurt Stüwe; Finlay M. Stuart; Nathan Cogne; David M. Chew; Jörg Robl (Earth and Planetary Science Letters, 2023)

Binary mixing of lithospheric mantle and asthenosphere beneath Tengchong volcano, SE Tibet: evidence from noble gas isotopic signatures - Kefei Chen; Huaiyu He; Finlay Stuart; Shaolin Liu; Xiwei Xu; Zhihui Cheng; Dinghui Yang; Jiyong Li; Fei Su; Wenshuai Wang (International Geology Review, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

In situ cosmogenic 10Be, 26Al, and 21Ne dating in sediments from the Guizhou Plateau, southwest China - Ye Yang; Yu Liu; Yan Ma; Sheng Xu; Cong-Qiang Liu; Shi-Jie Wang; Finlay M. Stuart; Derek Fabel (Science China Earth Sciences, 2021)

The performance of the Noblesse multi-collector noble gas mass spectrometer for 40Ar/39Ar geochronology - Defeng He; Finlay M. Stuart; Dan N. Barfod; Fang Xiao; Hong Zhong (Acta Geochimica, 2018)

The use of in-situ cosmogenic 21Ne in studies on long-term landscape development - Yan Ma; Finlay M. Stuart (Acta Geochimica, 2018)